A ROAD MAP FOR IMPLEMENTING SERVICE ORIENTED AGRICULTURAL INFORMATION MANAGEMENT SYSTEM - R. Akbar; M. F. Hassan; A. Abdullah; M. E. Babar; S. Safdar (Journal of Animal and Plant Sciences, 2012)
The advent of most modern and advanced tools and technologies in the field of information technology has brought revolutionized changes in all fields of our society. Traditional systems have been outdated and increasingly being replaced with new systems, applications and techniques. Almost all public and private sectors are updating themselves with modern information retrieval and management systems. Very sophisticated information systems have been implemented in various sectors. Unfortunately, in Pakistan agriculture is one of the fields in which information systems are not implemented as required. Limitations of resources and poor infrastructural facilities arise the need to rely on information systems in the agriculture sector in Pakistan. In this paper we have presented a road map for implementing an agricultural information system in Pakistan. The proposed system is a distributed service based information system for agriculture sector. Distributed framework is designed and implemented through service oriented architecture (SOA). The communications among the remote components of the system is done through service (component) calls using xml. The outcome of this research is to provide a basic road map to implement a service oriented agricultural information system to link all the agriculture related departments in Pakistan. It would help farmers, researchers, academicians, public and private sectors in information retrieval and sharing. The system is the potential solution of resource limitations and other problems being faced by agriculture sector in Pakistan.
Keywords: Agile; Distributed; Globalization; Information System; Service Oriented